2016
DOI: 10.1001/jamacardio.2016.3591
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Outcomes of Pulmonary Arterial Hypertension–Related Hospitalizations in the United States

Abstract: Analyses of temporal changes in PAH care reveal a significant decrease in PAH-related hospitalizations in the United States, but hospital charges have increased substantially and are increasingly being borne by Medicare. In-hospital mortality remains unchanged, but length of hospitalization has increased. This study should help identify the characteristics of patients with PAH that are associated with increased risk of in-hospital mortality and longer length of hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
73
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 28 publications
8
73
0
1
Order By: Relevance
“…Thus, coronary arteries in PAH are remodeled independently of their localization within the heart. Interestingly, when investigating the clinical characteristics of our patients with PAH (Table I in the online-only Data Supplement), we observed that 23% of our patients with PAH received a diagnostic of CAD, which corresponds to what was observed in the study by Anand et al 30 and that close to half of them also exhibited risk factors for developing the disease. Furthermore, when looking at the autopsy reports, an additional 23% of the patients with PAH had CAD and these numbers do not include coronary MVDs.…”
Section: Patients With Pah Exhibit Increased Coronary Wall Thicknesssupporting
confidence: 84%
See 1 more Smart Citation
“…Thus, coronary arteries in PAH are remodeled independently of their localization within the heart. Interestingly, when investigating the clinical characteristics of our patients with PAH (Table I in the online-only Data Supplement), we observed that 23% of our patients with PAH received a diagnostic of CAD, which corresponds to what was observed in the study by Anand et al 30 and that close to half of them also exhibited risk factors for developing the disease. Furthermore, when looking at the autopsy reports, an additional 23% of the patients with PAH had CAD and these numbers do not include coronary MVDs.…”
Section: Patients With Pah Exhibit Increased Coronary Wall Thicknesssupporting
confidence: 84%
“…Furthermore, a recent study analyzed trends and outcomes in PAH-related hospitalization in the United States and observed an increase in associated comorbid conditions in patients with PAH between the years 2001 and 2012, such as diabetes mellitus, hypertension, and CAD. 30 During that decade, CAD in patients with PAH increased from 15.6% to 22.3%, in addition to an increase in diseases considered as risk factors for coronary diseases. This concept is not surprising because PAH is now recognized not to be restricted to the lungs.…”
Section: P Ulmonary Arterial Hypertension (Pah) Is a Vascularmentioning
confidence: 99%
“…There was a trend towards admission of patients greater than 65 years of age that is in line with all recent studies that found a shift in diagnosis of PH to an older age [13,[18][19][20]. Most patients continued to be women in both 2000 and 2013.…”
Section: Age Characteristics and Payer Statussupporting
confidence: 87%
“…This was in spite of the fact that a recent study reported a decline in the number of hospitalizations associated with PAH (Group 1) alone from 2001 through 2012 [13]. This would indicate that the rise in the number of hospitalizations due to PH can actually be attributed to an increase in admissions due to secondary causes of PH i.e.…”
Section: Discharges and Length Of Staymentioning
confidence: 81%
See 1 more Smart Citation